Transmission of Stenocarpella maydis by maize seeds - Siqueira, Carolina; Barrocas, Ellen; Machado, José; Corrêa, Carla (Revista Ciência Agronômica, 2016)
Stenocarpella maydis is one of the main fungi associated with maize seeds, being a causative agent of stalk and ear rot, a disease which causes considerable losses for crop-producing regions in Brazil. The organism is considered to be a pest, subject to sanitary standardisation in current programs of seed certification in the country. The aim of this study was to evaluate the transmission rate of the fungus from infected maize seeds. Seeds were inoculated with two isolates using a method of physiological conditioning, in which the seeds are kept in contact with colonies of the fungus for 24 (P1), 48 (P2), 72 (P3) and 96 (P4) hours. Two cultivars were used, one susceptible (C1) and one moderately resistant (C2), and the trial carried out at two temperatures (20 °C and 25 °C). The inoculated seeds were distributed individually into plastic cups containing substrate. The plants were evaluated daily for stand and the appearance of post-emergent symptoms. Based on the number of dead seeds, transmission rates reached a maximum of 90.5% at the P4 inoculum potential, this rate being greater than transmission rates achieved for symptomatic and asymptomatic infection in emerged plants. For the total transmission rate, transmission of the pathogen was seen at all inoculum potentials; these values varying from 25% for cultivar C2 at potential P1 and a temperature of 20 °C, to 93% for cultivar C2 at potential P3 and a temperature of 25 °C.